Caesarean Delivery Rates in Birth Centres: confrontation using Robson Classification. (13th November 2019) - Bocci, G; Nante, N; Napolitani, M; Scinicariello, I; Kundisova, L; Messina, G; Alaimo, L
Abstract: Background: A caesarean section (CS) is a life-saving procedure, reducing perinatal mortality and morbidity, over last decades CS rates are increasing. In 2015 the Robson classification (RC) was introduced by WHO as a global standard for assessing, monitoring and comparing CS rates within healthcare facilities and between them. The aim of this cross-sectional study was to identify the most numerous groups according to RC. Methods: All women, who delivered by CS from January 2015 to June 2017 in two hospitals in the province of Siena (Italy): I level Birth Centre of Grosseto (GR) and II level Birth Centre of Siena (SI) were included. Age, type of hospital and group based on RC were extracted from Medical Register. The RC divides women into 10 groups based on 5 basic obstetric characteristics (parity, number of foetuses, previous CS, onset of labour, gestational age, foetus presentation). The percentages of the group's contribution to the overall CS rate were calculated and confronted for two birth centres. All analysis was performed with Stata. Results: A total of 2115 women was analysed, 50.5% from SI. Average age was 34.3±5.7; significantly higher for SI (34.7±5.6vs33.9±5.8). Most contributing groups were group V: multiparous, singleton, cephalic, term, with previous CS (24.2%), group II: nulliparous, singleton, cephalic, term, induced labour or CS (24%), group I: nulliparous, singleton, cephalic, term, spontaneous labour (11.45%), group VIII: multiple pregnancy (10.7%) and group X: singleton, cephalic, pre-term (10.4%). Differences for type of birth centre were observed for groups I, II, V and VIII: I and VIII were more numerous in SI, II and V in GR (chi2; p < 0.05). Conclusions: The most numerous groups were I, II e V, concordant with literature. Reduction of CS rates in group V could be obtained through lowering of primary CS rates and by promotion of Vaginal Birth After CS. Healthcare professionals could help to reduce labour-related anxiety and elective CS rates. Key messages: The most contributing groups to overall caesarean section rates were groups I, II e V, as reported in literature. Reduction of CS rates could be obtained through lowering rates of primary CS, but also by promotion of Vaginal Birth After CS.